Oxidation of nickel-base welds 182 and 82 in simulated primary water of pressurised water reactors. (January 2015) - Wehbi, M.; Couvant, T.; Duhamel, C.; Crepin, J.
Abstract : To date, nickel-base welds 182 and 82 used in pressurised water reactors have shown a higher susceptibility to stress corrosion cracking (SCC) during laboratory tests than in power plants. However, the increasing number of cracks reported in American, Swedish and Japanese nuclear power plants on Alloys 182/82 enlightens the need for a predictive initiation model of SCC. Initiation of SCC involves several variables interacting together such as material microstructure and composition, primary water chemistry and loading history. Building such a model requires studying each contribution of individual phenomenon, in order to have a better understanding of the mechanisms involved at a local scale in crack initiation. Before SCC initiation, some grain boundaries exposed to primary water present intergranular oxidation reaching several hundreds of nanometres. The oxide penetration kinetics could be modified by several parameters such as local metallurgy, dissolved hydrogen content of the primary water and mechanical history before oxidation. The grain boundaries affected by oxidation during a tensile test demonstrate a lower resistance to failure compared to 'healthy' grain boundaries. The main objective of this study is to determine key local parameters controlling grain boundary oxidation in order to calibrate an oxidation model which will be integrated to SCC initiation modelling.